A partial derivatives approach for estimation of the viscosity Arrhenius temperature in N, N-dimethylformamide + 1, 4-dioxane binary fluid mixtures at temperatures from 298.15 K to 318.15 K. (2nd September 2016) - Al-Omair, N. A.; Das, D.; Snoussi, L.; Sinha, B.; Pradhan, R.; Acharjee, K.; Saoudi, K.; Ouerfelli, N.
ABSTRACT: Excess properties calculated from the literature values of experimental density and viscosity in N, N-dimethylformamide (DMF) + 1, 4-dioxane (DO) fluid binary mixtures (from 303.15 to 318.15) K can lead us to test the different correlation equations as well as their corresponding relative functions. Inspection of the Arrhenius activation energy Ea and the enthalpy of activation of viscous flow ∆ H * shows very close values; here we can define partial molar activation energy Ea 1 and Ea 2 for DMF and DO, respectively, along with their individual contribution separately. Correlation between the two Arrhenius parameters of viscosity in all compositions shows the existence of the primary distinct behaviours separated by particular mole fractions in DMF. In addition, we add that the correlation between Arrhenius parameters reveals interesting Arrhenius temperature ( TA ), which is closely related to the vaporisation temperature in the liquid–vapour equilibrium; moreover, the limiting corresponding partial molar properties allow us to estimate the boiling points of the pure components.